Morphological and Histological Changes in Ligamentum Flavum in Degenerative Lumbar Canal Stenosis in Indian Population (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: spinal canal stenosis; ligamentum flavum calcification; ligamentum flavum hypertrophy